Low and High Gas Tungsten Arc Welding Heat Inputs Influence on Corrosion of Stainless Steel Weldments - Kutelu, Bolarinwa Johnson; Oyetunji, Akinlabi; Oloruntoba, Daniel Toyin (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
In this study, influence of low and high heat inputs on corrosion susceptibility of 304L austenitic stainless steel (ASS) in simulated 0.5 molar solution of NaCl was investigated. Gas tungsten arc welding (GTAW) was used to generate low and high levels welding heat input. Microstructures of the weldments were examined, using metallurgical optical microscope (OMM) (Olympus GX51), while the corrosion behaviours were evaluated by potentiodynamic polarization tests, and corrosion data were recorded, using a computer-based data logging system – Autolab PGSTAT 204N. From the results, the evolving microstructures of the weldments before corrosion were characteristically heterogeneous; austenite (γ) was the leading phase, while ferrite (α) grains were dispersed within the γ matrix. Fusion zone (FZ) and heat affected zone (HAZ) microstructures after corrosion were characterised by pits of varying sizes with different alignments. And at GTAW speed, current and voltage of 7.2 mm/s, 200A and 40V, corresponding to low heat inputs, there were few number and size of pits relative to 1.7 mm/s, 200A and 40V, corresponding to high heat input. Shift in corrosion potentials (Ecorr) toward less negative direction, that is more nobility was observed at the low heat inputs induced GTAW parameters as compared to the corresponding high heat inputs induced GTAW parameters. In general, corrosion susceptibility of 304L ASS in the simulated 0.5 molar solution of NaCl was heightened at high heat inputs induced GTAW parameters as compared to the corresponding low heat inputs parameters.